Impact of biological sex on the outcomes of spinal cord stimulation in patients with chronic pain. Issue 4 (9th December 2021) - Mekhail, Nagy; Costandi, Shrif; Saweris, Youssef; Armanyous, Sherif; Chauhan, Gaurav
Abstract: Background: Spinal cord stimulation (SCS) continues to gain increasing popularity in the pain management field for the treatment of different painful conditions; however, to‐date, the correlation between the SCS effectiveness and biological sex has not been fully established. We aimed to investigate the correlation between the biological sex and SCS outcomes. Methods: Following Institutional Review Board approval, a retrospective cohort study was performed by collecting data for patients treated with SCS at a tertiary academic center between the years 2002 and 2019. Data was assessed with multivariable linear regression to investigate the association between biological sex and pain scores at baseline, 6‐, and 12‐ months following SCS implantation. Propensity score matching (PSM) was performed based on a set of covariates including age, duration of pain, time since implant, BMI, opioid medications use, smoking, depression and history of alcohol, or substance abuse. Results: Of the patients treated with SCS implants, 418 patients fit the inclusion and exclusion criteria, out of which the majority were females (272, 65%). The pre‐matching data reported a significant difference in history of diabetes and depression and was also significant for greater opioid use in male patients at baseline, 6‐, and 12‐months post‐SCS implant. Propensity score matching (PSM) was performed based on the above mentioned covariant. After matching, no statistical difference was found among the variables, in both groups. Furthermore, after matching no significant differences in the pain scores at baseline, 6‐, and 12‐months post‐SCS implant were observed. Conclusion: No biological sex‐based differences in the analgesic response to SCS therapy was detected at 6‐ and 12‐months post‐SCS implant between groups with similar demographics, biomedical, and psychological values.